PTU-237 Band on the run: no follow up appointments required after rubber band ligation of haemorrhoids?. (22nd June 2015) - Blackwell, J; Bhalla, A; Mitchell, J; Williams, J; Lund, J
Abstract : Introduction: Several surgical options exist for the treatment of haemorrhoids, with rubber band ligation (RBL) being the commonest. Long term outcome data for RBL is sparse. We investigate the effectiveness of RBL haemorrhoids in the outpatient setting. Method: Data for consecutive patients undergoing RBL of haemorrhoids between January 2013–January 2014 was collected retrospectively. Patients were followed up for a minimum of one year with specific data collected for previous treatments, proctoscopic appearances, and outcomes after RBL. Results: Two hundred and sixty four patients [145 males, median age 52 years (range 19–94)] underwent RBL. In 177 this episode of RBL was their first intervention for haemorrhoids, with the remaining patients having previously had several different treatments including RBL (31%, n = 81), surgery (3%, n = 7) and sclerotherapy (<1%, n = 1). Median time between previous treatments and RBL was 1 year (range 1 month- 30 years). The number of haemorrhoids was noted in 65% of patients (n = 177; solitary haemorrhoid 23% n = 40, multiple haemorrhoids 77% n = 137). Grade was recorded in 94/264: 1% Grade I (n = 11), 26% Grade II (n = 46), 19% Grade III (n = 33), 2% Grade IV (n = 4). Post RBL 88% (n = 231) of patients were offered 10 week open outpatient appointment as per local protocol, 11 patients (4%) were discharged and 22 (8%) were given specific dates for follow up (median 10 months (range 4–20 months)). 17% required further investigation: endoscopy in 16% (n = 44, where 37/44 were patients over the age of 50 years which follows local protocol for rectal bleed), defecating proctography in 2 patients and CT pneumocolon in 2 patients. At 1-year post RBL 72% (n = 192) of patients had not returned, but the remaining 72 were re-referred (mean time 8 months, standard deviation 154 days) with recurrent symptoms. Further treatment was with repeat RBL (n = 30) and surgery (n = 33), 1 patient referred to dermatology, one patient was referred to gastroenterology with proctitis. Seven patients returning to clinic either declined further banding or data was unavailable. Conclusion: Patients presenting with haemorrhoids can be treated with RBL and then discharged (notwithstanding local protocols for exclusion of malignancy in patients over a certain age with PR bleeding). Three quarters will not return with further symptoms and the remainder will not represent for a year, so making planned follow up unnecessary. Disclosure of interest: None Declared.